2021
DOI: 10.1007/s00170-021-07500-w
|View full text |Cite
|
Sign up to set email alerts
|

Towards optimization of thickness, hardness, and porosity of low-pressure cold sprayed WC-Ni coatings

Abstract: In this study, a 3 3 full factorial design methodology was used to analyze the effects of spray parameters on the thickness, hardness, and surface porosity of low-pressure cold-sprayed WC-17Ni coatings. Three levels were selected for the spray parameters included in the design which were the powder feed rate (17.1 g/min, 21.1 g/min, and 23.7 g/min), gas temperature (475℃, 500℃, and 525℃), and the nozzle to substrate stand-off distance (3 mm, 5 mm, and 10 mm). It was found that the feed rate was the most signi … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…In general, all parameters impact on the characteristics of the deposit. The prominent parameters 7 Journal of Nanomaterials that had a higher impact on the deposit were chosen based on previously published work [18,19]. The selected factors are temperature, SOD, and powder feed rate.…”
Section: Identification Of Processmentioning
confidence: 99%
“…In general, all parameters impact on the characteristics of the deposit. The prominent parameters 7 Journal of Nanomaterials that had a higher impact on the deposit were chosen based on previously published work [18,19]. The selected factors are temperature, SOD, and powder feed rate.…”
Section: Identification Of Processmentioning
confidence: 99%
“…Although heavily studied, WC-Co particles continue to fascinate the research community, being recently found also as matrix material in carbon nanotubes [ 40 ] or in TiC-based hot-pressed composites [ 41 ]. The cermet particles are commonly incorporated in a matrix material, being very often deposited through various thermal spraying techniques such as plasma [ 40 , 41 ], cold gas [ 42 , 43 , 44 ], high-velocity oxy-fuel [ 35 , 45 , 46 , 47 ], air-fuel [ 48 , 49 , 50 ], spraying, or even by a process combining the last two [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Многие работы посвящены получению композиционных покрытий методом холодного газодинамического напыления из порошковой смеси заданного состава (см., например, [2][3][4][5][6]). Традиционно подготовка композиционных смесей осуществляется с использованием вибростенда или V -образного смесителя.…”
unclassified